(untitled) (Mustansiria Dental Journal, 2018)
Background: In spite of advances in dentistry, anxiety about dental treatment and the fear of pain remains public health problem and is a significant impediment to dental treatment. The purpose of this study was to assess the levels of dental anxiety in patients who referred to Al-Mustansiriyah dental clinics and Al-Shiekh Omar specialized dental center in Baghdad and their relation to their gender, age, educational level. Materials and methods: The study was done on (800) patients, aged (20-59) years in Baghdad. The survey form was prepared and translated from English to Arabic languages by certified translator and were filled by patients themselves without any help from dentists. Patients with mental retarded, those who not having completed the survey form and those below 20 years and above 59 years were excluded. The survey was divided into 3 parts (socio-demographic information, Modified dental anxiety scale (MDAS) and Dental fear survey (DFS). Results: The present study showed that females had higher anxiety (13.57, 47.38) than males (8.98, 37.75) for Modified dental anxiety scale and Dental fear survey respectively. The anxiety decreased with advance of age (12.31, 11.41, 10.89, 10.45 for Modified dental anxiety scale and 43.10, 41.22, 38.69, 37.93 for Dental fear survey) in groups (1,2,3,4) respectively. The anxiety decreased with advance of teaching, so the uneducated patients had higher mean of anxiety (14.45, 48.59) while the postgraduate patients had lower anxiety (9.10, 36.30) for Modified dental anxiety scale and Dental fear survey respectively than others. There was high significant difference between males and females at P-value (≤ 0.01) for both Modified dental anxiety scale and Dental fear survey scales. Analysis of variance (ANOVA) test showed high significant difference among age groups and among education level groups at P-value (≤ 0.01) for both Modified dental anxiety scale and Dental fear survey scales. The higher percentage of anxiety scales was appeared in minimal anxiety score in males (56%, 48%) in Modified dental anxiety scale and Dental fear survey respectively, while lessor percentage was appeared in very high anxiety score in males (5.1%, 5.5%) in Modified dental anxiety scale and Dental fear survey respectively. Pearson’s correlation coefficient (R) showed that there was a positive relationship between gender and anxiety scales, with statistically high significant at P-value (≤ 0.01). While, there was inverse relationship between age and anxiety scales, and between education and anxiety scales with statistically high significant at P-value (≤ 0.01) for both relations. Conclusion: The females had higher rate of anxiety than males. The anxiety decreased with advance of age and education level of patients. There was a strong (positive) relationship between gender and anxiety. While, there was inverse (negative) relationship between anxiety with age and education.